Structures of the Human HCN1 Hyperpolarization-Activated Channel - Lee, Chia-Hsueh; MacKinnon, Roderick (Cell, 2017)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels underlie the control of rhythmic activity in cardiac and neuronal pacemaker cells. In HCN, the polarity of voltage dependence is uniquely reversed. Intracellular cyclic adenosine monophosphate (cAMP) levels tune the voltage response, enabling sympathetic nerve stimulation to increase the heart rate. We present cryo-electron microscopy structures of the human HCN channel in the absence and presence of cAMP at 3.5 Å resolution. HCN channels contain a K+ channel selectivity filter-forming sequence from which the amino acids create a unique structure that explains Na+ and K+ permeability. The voltage sensor adopts a depolarized conformation, and the pore is closed. An S4 helix of unprecedented length extends into the cytoplasm, contacts the C-linker, and twists the inner helical gate shut. cAMP binding rotates cytoplasmic domains to favor opening of the inner helical gate. These structures advance understanding of ion selectivity, reversed polarity gating, and cAMP regulation in HCN channels. [Display omitted] •Structures of the human HCN1 hyperpolarization-activated channel at 3.5 Å resolution•Channel filter adopts a unique conformation, allowing both K+ and Na+ to permeate•Long S4 helix and unusual coupling to the pore mediate reversed polarity gating•Cyclic AMP induces a rotation of cytoplasmic domains to favor channel opening Cryo-EM structures of the human HCN1 hyperpolarization-activated ion channel provide mechanistic insights on voltage-dependent gating with reversed polarity.